Fenestrated and Branched Stent-Grafts for the Treatment of Thoracoabdominal Aortic Aneurysms: A Systematic Review and Meta-Analysis - Hu, Zhongzhou; Zhang, Zheng; Liu, Hui; Chen, Zhong (Frontiers in Cardiovascular Medicine, 2022)
Purpose: To investigate the safety and efficacy of total endovascular repair for thoracoabdominal aortic aneurysms (TAAAs) with fenestrated and branched stent-grafts. Methods: The MEDLINE, EMBASE, and Cochrane databases were searched between January 2001 and December 2021 to identify literature relevant to the use of fenestrated and branched endografts for the treatment of TAAAs. Studies with <4 cases and those on juxtarenal or pararenal aortic aneurysms were excluded. Meta-analyses were conducted to evaluate spinal cord ischemia (SCI), irreversible SCI, renal insufficiency, dialysis, endoleak, reintervention, target vessel patency, 30-day mortality and overall mortality. Fourteen studies comprising 1114 patients (mean age 72.42 years, 847 men) were selected. The mean TAAA diameter was 67 mm. The Crawford TAAA classification was type Ⅰ-III in 759 cases, type Ⅳ in 344 cases, and type V in 10 cases. Outcomes of the meta-analysis are reported as proportions and 95% confidence intervals (CIs). Results: The pooled rates for 30-day mortality and overall mortality were 6% and 18%, respectively. The pooled rate for technical success was 94% (95% CI, 93%-96%), for SCI was 8% (95% CI, 7%-10%), for irreversible SCI was 6% (95% CI, 4%-7%), for renal insufficiency was 7% (95% CI, 5%-10%), for dialysis was 3% (95% CI, 2%-4%), for endoleak was 14% (95% CI, 8%-26%), for target vessel patency was 98% (95% CI, 97%-99%), and for reintervention was 15% (95% CI, 9%-24%). Conclusion: Fenestrated and branched endografts for the treatment of TAAAs are safe and effective with acceptable early results. However, defects such as relatively high rates of branch-related endoleaks and restrictions on patient selection should be considered. Lifelong regular follow-up and additional prospective studies are necessary to substantiate whether this technique is valid.